Quality of Life and Sense of Coherence in Cancer Patients of German, Turkish and Polish Origin—A Cross-Sectional Study - Lieb, Marietta; Erim, Yesim; Morawa, Eva (International Journal of Environmental Research and Public Health, 2023)
Background: Due to a variety of symptoms and side-effects of cancer treatment, quality of life can be considerably impaired in cancer patients. Especially, cancer patients with a migration background seem to be at risk. The objective of our study is to investigate the quality of life and sense of coherence in adult cancer patients of German, Turkish and Polish origin. Methods: We assessed sociodemographic, migration-specific and cancer-related parameters. Quality of life was measured via the EORTC QLQ-C30, sense of coherence was measured with the SOC-13. Results: We included 227 patients in the study (59.5% native Germans, 40.5% with migration background). Native Germans did not differ in quality of life compared to all migrants. However, more nausea and vomiting (NV) and higher appetite loss (AP) was found in Turkish migrants compared to Polish migrants and native Germans. For sense of coherence, we observed significantly higher scores for native Germans compared to all migrants. Turkish migrants had significantly lower scores compared to native Germans. Conclusions: A Turkish migration background seems to play an important role in the perception of symptoms, especially of nausea and vomiting and appetite loss. Culture-specific aspects should be considered in cancer care.
CRIS-Team Scopus Importer:2023-02-24
Keywords: cancer; German; migration background; Polish; quality of life; sense of coherence; Turkish